The Balance of Payments Impact of the Food and Fuel Price Shocks on Low-Income African Countries : A Country-by-Country Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This note discusses the implications of the price shocks for the balance of payments of low-income countries in sub-Saharan Africa. The response by bilateral donors and multilateral institutions will, in practice, need to be country-specific. To this end, the note identifies a list of 18 countries in the region that are especially hard-hit and that consequently face a pressing need for additional balance of payments and budget support. The list reflects country circumstances and underlying assumptions as of May, and is subject to change; it is not meant to be definitive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet